Analisis Faktor yang Mempengaruhi Harga Saham - Wenny Anggeresia Ginting (Politeknik Ganesha Medan, 2018)
This research is raining to know and analyze the influence of Net Profit, Earning Per Share, and Return On Asset to stock price in property and real estate company listed in Indonesian stock exchange in 2012-2015 either simultaneously or partially. The method used in this research is quantitative descriptive with multiple linear regression analysis technique which aim to know the amount of regression coefficient showing the influence of variable of Net Profit, Earning Per Share, and Return On Asset to stock price. The data used is secondary data. The number of samples used in this study were 80 companies. This study uses multiple linear regression analysis to see the effect of independent variables on the dependent variable. The results showed that simultaneously, Net Profit, Earning Per Share, and Return On Asset effect on Stock Prices on property and real estate companies listed on the Indonesia Stock Exchange for the period 2012-2015. And partially also can be seen that the variable Net Profit, Earning Per Share, and Return On Asset effect on Stock Prices on property and real estate companies listed on the Indonesia Stock Exchange for the period 2012-2015.